2009
DOI: 10.1088/0031-9155/54/14/015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization and system simulations of depth of interaction PET detectors using 0.5 mm and 0.7 mm LSO arrays

Abstract: Small animal PET scanners may be improved by increasing the sensitivity, improving the spatial resolution and improving the uniformity of the spatial resolution across the field of view. This may be achieved by using PET detectors based on crystal elements that are thin in the axial and transaxial directions and long in the radial direction, and by employing depth of interaction (DOI) encoding to minimize the parallax error. With DOI detectors, the diameter of the ring of the PET scanner may also be decreased.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…This suggests that the lower bound of crystal width stays close to 1.5 mm, if the Anger-logic scheme with light sharing (multiplexing ratio: 16 to 1) and L(Y)SO crystals ( $ 13-20 mm height) are to be used. Here, it is worthwhile emphasizing that such conclusion does not contradict with those previous studies in which PET detectors of crystals less than 1 mm width have been successfully demonstrated [13][14][15][16][17]. Instead, our study explains the necessity of a number of design alternatives deployed in other studies to help push the limit of spatial resolution towards submillimeter, such as: (1) using a one-to-one coupling scheme without any electrical/optical multiplexing; (2) reducing the multiplexing ratio to be less than 16:1; (3) reducing crystal height to improve photodetector SNR at the cost of detection efficiency for 511 keV photons; or (4) using position-sensitive sensors (such as PSPMTs based on internal multi-anodes or PSPADs based on an internal resistive sheet).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…This suggests that the lower bound of crystal width stays close to 1.5 mm, if the Anger-logic scheme with light sharing (multiplexing ratio: 16 to 1) and L(Y)SO crystals ( $ 13-20 mm height) are to be used. Here, it is worthwhile emphasizing that such conclusion does not contradict with those previous studies in which PET detectors of crystals less than 1 mm width have been successfully demonstrated [13][14][15][16][17]. Instead, our study explains the necessity of a number of design alternatives deployed in other studies to help push the limit of spatial resolution towards submillimeter, such as: (1) using a one-to-one coupling scheme without any electrical/optical multiplexing; (2) reducing the multiplexing ratio to be less than 16:1; (3) reducing crystal height to improve photodetector SNR at the cost of detection efficiency for 511 keV photons; or (4) using position-sensitive sensors (such as PSPMTs based on internal multi-anodes or PSPADs based on an internal resistive sheet).…”
Section: Discussionsupporting
confidence: 58%
“…The results indicate that 500 mm FWHM resolution could be achieved if 250 mm crystal elements and an 8 cm system diameter can be made. On the experimental side, several groups have made extensive efforts to develop high-resolution PET detectors (crystal width: $ 0.5-1 mm) [13][14][15][16][17]. However, most of these designs are implemented based upon either position-sensitive (PSPMTs) or position-sensitive APDs (PSAPDs), and differ from the Anger-logic scheme studied in our work with regard to both multiplexing ratio (i.e., less than 16:1) and light sharing (i.e., not using an optical diffuser).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 There is a growing trend of going toward finer crystal pixelation to improve spatial resolution, specifically in preclinical or dedicated brain PET systems. 5,[30][31][32][33] Using radially long scintillation crystals to maximize the detection sensitivity of the PET camera increases the parallax error 34,35 and degrades the system's spatial resolution, 28 especially at trans-axial distances far from the center field of view (FOV). Additionally, by accepting bigger ring differences for coincident events along the axial FOV, the parallax error causes distortions in the reconstructed image.…”
Section: Introductionmentioning
confidence: 99%
“…Another feature of the detection module is the Depth of Interaction (DOI) information related to the z coordinate of the gamma rays inside the crystal. This reduces the parallax error in the determination of the LOR by minimizing errors due to non-collinearity of the annihilation photons [9]. Furthermore, both the arrival time and the energy of the events are measured by integrated readout electronics in order to implement a compact detection module which can be used as a basic element for a PET ring.…”
Section: D-mpet Projectmentioning
confidence: 99%